Are Pre-Service Science Teachers Professionally Ready? Achievement Profile and Equity Analysis Across Class Types in a Teaching Profession Course - Salma Samputri (MO.RI Publishing, 2026)
The Teaching Profession course serves as a foundational subject in developing professional competencies for pre-service science teacher students. This study aimed to analyze the profile of professional competency achievement of pre-service science teachers through this course and to compare achievement outcomes across Regular Class A, Regular Class B, and the International Class Program (ICP) in the even semester of the 2025–2026 academic year at State University Makassar. A comparative quantitative design (ex-post facto) was employed, involving 100 students from three classes (Reg A: n=37, Reg B: n=33, ICP: n=30). Final course scores were analyzed descriptively and inferentially using the Kruskal-Wallis test, with Mann-Whitney U tests applied as supplementary pairwise comparisons. Results showed an overall mean score of 84.45 (SD=9.04), with the majority of students categorized as Good to Excellent. No significant difference was found in professional competency achievement across the three classes (H=0.533; p=0.766), with very small effect sizes across all pairwise comparisons (r<0.10). These findings indicate that professional competency attainment is equitable across class types, suggesting consistent and fair implementation of the Teaching Profession course. The study recommends strengthening student-centered learning strategies and developing comprehensive authentic assessments, including reflective portfolios, performance rubrics, and case-based tasks, to produce more robust evidence of professional competency attainment.